Bond performance of tensile lap-spliced basalt-FRP reinforcement in high-strength concrete beams - Islam Eltantawi (17151091) (2022)
This paper investigates the bond between high-strength concrete (HSC) and tensile lap-spliced basalt fiber-reinforced polymer (BFRP) bars. Ten large-scale BFRP-reinforced concrete beams (300 × 450 × 3900 mm) were fabricated and tested under four-point loading until failure. The parameters investigated included the BFRP bar diameter (10, 12, and 16 mm), the splice length (400–1200 mm range), and the bar surface texture (sand-coated (SC) and helically wrapped (HW)). Test results demonstrated that the flexural capacity of the beams reinforced with SC-BFRP bars was almost similar to that of beams reinforced with HW-BFRP bars. However, SC-BFRP bars showed a slightly higher bond with concrete compared to that of helically wrapped counterparts. The bond strength of spliced BFRP bars was inversely related to the splice length. Also, BFRP bars with larger diameter bars require longer splice lengths to reach their maximum capacity. Finally, the experimentally estimated critical splice lengths were compared to those calculated by existing models and code-based equations. Both ACI 440.1R-15 and CSA S806-12 provisions were conservative in predicting splice length for BFRP bars. However, the CSA-S6-14 design code was more accurate in estimating the splice length for BFRP with bigger diameters. Though, it was not conservative with smaller diameters. Other Information Published in: Composite Structures License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.compstruct.2021.114987